Formulation And Characterization Of Herbal Cream For The Management Of Acne Vulgaris - Sharma, Nidhi; Shrivastava, Pranjul; Tiwari, Sandip Prasad (Journal of Neonatal Surgery, 2025)
This study focused on the formulation and characterization of a herbal cream for the management of acne vulgaris, aiming to provide a natural, effective, and safer alternative to conventional synthetic treatments. Herbal extracts from (Neem), (Aloe vera), (Turmeric), (Green tea), and (Tulsi) were selected based on their established antimicrobial and anti-inflammatory properties. The final formulation exhibited excellent organoleptic properties with a smooth, white, uniform texture and pleasant herbal odour. The pH of the cream was recorded at ensuring compatibility with the skin’s natural pH range. Spreadability was measured at cm², indicating ease of application and uniform coverage. Viscosity was found to be suitable for topical application, contributing to both stability and user compliance. Stability studies conducted over two weeks at varied storage conditions room temperature refrigeration and accelerated revealed no significant changes in color, phase separation, or consistency, confirming the physical stability of the formulation. Antimicrobial activity, assessed via the agar well diffusion method, showed a zone of inhibition of against Propionibacterium acnes, the primary acne-causing bacterium. In comparison, a standard antibiotic showed a m inhibition zone against Staphylococcus aureus, highlighting the herbal cream's notable antibacterial efficacy despite its natural composition. These findings suggest that the herbal cream is a viable, safe, and effective alternative for the management of acne vulgaris